Building the supply of demand: Experiments in mini-grid demand stimulation. (2021) - Lukuyu, June; Fetter, Rob; Krishnapriya, P.P.; Williams, Nathan; Taneja, Jay
Abstract: Solar mini-grids are a key element in strategies to achieve universal access to modern energy by 2030. In many settings mini-grids offer a combination of affordability, reliability, and capacity for productive use of power, moreso than most solar home systems and some central grids. Yet the economic sustainability of mini-grids relies on achieving target usage levels, and consumption data to date suggest that they may be commercially unsustainable due to consistently low demand for power once installed—and that newly-connected recipients cannot take full advantage of access. Using a uniquely fine-grained data set spanning 29 villages in East Africa, we test whether credit constraints and the cost of electricity hinder demand growth among mini-grid-connected households. We find that households that purchased appliances under a financing program increased consumption by up to 66 percent compared to matched controls, though a sensitivity analysis suggests this estimate is rather sensitive to bias from unobservable characteristics, and the increase is not sustained. While most customers in the program do not repay loans in full, we find that on average, customers repay about 78 percent of the loan amount. When we analyze developers' return on investment, we find that the profitability of appliance financing programs at a market cost of capital, similar to those evaluated in this study, depends substantially on the types of appliances on offer. With a limited sample size, the tariff subsidy program indicated that lowering the cost of electricity by up to 75 percent substantially increased consumption, albeit with mixed signals for whether overall revenue could be maintained at a lower tariff, therefore calling for further research to find the optimal balance of affordable tariffs and profitable business models for mini-grids in settings like East Africa. Highlights: Minigrids are key to achieving universal access to modern energy by 2030. Credit constraints hinder demand growth among minigrid-connected households. Profitability of appliance financing programs hinges on type of appliances offered. Mini-grid customers are highly sensitive to changes in the price of electricity.